Olanzapine for managing side effects from tyrosine-kinase inhibitors - Muniz, Miguel; Peskey, Candy; Jatoi, Aminah; Ruddy, Kathryn Jean; Orme, Jacob; Pagliaro, Lance C.; Quevedo, Fernando; Costello, Brian Addis; Megan, Spychalla; Heath, Elisabeth I.; Zakharia, Yousef; Singh, Parminder; et al. (Journal of clinical oncology, 2025)
524Background: Antiangiogenic tyrosine kinase inhibitors (TKIs) play a key role in treating renal cell carcinoma and other solid organ malignancies, but TKIs cause bothersome side effects that frequently necessitate dose reductions or treatment holds. Olanzapine has been useful for palliating symptoms from classical chemotherapies and advanced cancer, but its effect on TKI-related symptoms is largely unknown. This retrospective study aimed to estimate the efficacy of olanzapine for TKI-induced nausea, vomiting, anorexia, weight loss, and insomnia. Methods: All patients prescribed olanzapine with lenvatinib, cabozantinib, axitinib, or tivozanib at Mayo Clinic between January 1, 2018, and June 30, 2024 were assessed for inclusion. For baseline symptom assessment, clinical care team notes documenting the presence or absence of symptoms and indication(s) for starting olanzapine were reviewed. For response assessment, clinical notes and patient portal messages from the first three months after starting olanzapine were evaluated for qualitative descriptions of change in symptom burden. Relevant data were extracted as direct quotations, which were reviewed by the research team and categorized as "improved," "worsened," "stable," or "missing data." Each symptom domain was analyzed independently when olanzapine was prescribed for multiple interrelated symptoms. Results: A total of 60 patients who received olanzapine for the treatment of TKI-related adverse effects were included. The most common documented indication for olanzapine was nausea without vomiting (n=35), followed by anorexia (n=25), nausea with vomiting (n=16), weight loss (n=16), and insomnia (n=11). In 32 cases (53%), olanzapine was prescribed for multiple, simultaneous symptoms. Response rates for each symptom domain are shown in the table. In addition, prior to olanzapine, 34 patients (57%) had documented weight loss. Following olanzapine, 50% (n=17) gained weight (median increase: 6.1 kg; range: 2.0 - 10.7 kg), 26% (n=9) stabilized their weight (±1 kg), and 24% (n=8) continued to lose weight. Clinicians utilized a TKI dose reduction within one week of olanzapine initiation in 5 cases (8.3%), and 3 of these patients could resume the higher dose of TKI after starting olanzapine. Only 4 patients (7%) discontinued olanzapine within 3 months due to perceived side effects. Conclusions: Olanzapine appears to be effective in treating TKI-induced nausea, vomiting, anorexia, insomnia, and weight loss. Prospective randomized placebo-controlled studies are needed to confirm these findings.Improvedn (%)Worsened n (%)Stablen (%)Missing Datan (%)Nausea without emesis32 (84)3 (8)1 (3)2 (5)Nausea with emesis13 (93)0 (0)0 (0)1 (7)Anorexia26 (74)2 (6)4 (11)3 (9)Insomnia11 (85)0 (0)2 (15)0 (0)